Oyster-dominated macrobenthic associations in the Cenomanian of Djebel Bouarif (Aures Mountains, Northeastern Algeria) - Aouissi, Riadh; Abdelhady, Ahmed Awad; Martinez, Sergio; Ahmed, Mohamed S.; Hannaa, Wagih; Jain, Sreepat; Salmi-Laouar, Sihem (Cretaceous Research, 2023)
In the Batna area of Algeria, the Cenomanian is represented by the Smail Marls Formation, a highly fossiliferous unit with a diverse benthic macrofauna (mainly of ostreid bivalves). A total of 1090 specimens belonging to 65 macrobenthic species were identified from 19 stratigraphic samples. The macrofaunal communities were quantitively analyzed using the hierarchical clustering (HC), nonmetric multidimensional scaling (NMDS), and permutational analysis of variance (PERMANOVA). Five distinct associations are recognized: 1) Costagyra olisiponensis, 2) Rhynchostreon suborbiculatum, 3) Aspidiscus cristatus, 4) Rhynchostreon suborbiculatum-Mecaster ameliae, and 5) Pycnodonte vesicularis. Data suggests that during the Cenomanian, the dominance of high-energy opportunistic oyster species within the soft marly sediments are related to their adaptive strategies. The changes noted in the community structure are attributed to sea-level fluctuations, rate of sedimentation and the prevailing hydrodynamics. Towards the uppermost Cenomanian and the Cenomanian–Turonian boundary, the oysters become rare due to eustatic sea-level rise and this decline coincides with increasing predation intensity on oysters and the destruction of their shallower habitats.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Benthic associations; Bivalves; North Africa; Paleoenvironmental reconstruction; Upper Cretaceous